The girl who survived - Jackson, Lisa (New York, NY : Kensington Publishing Corp., 2022)
The sole survivor of a brutal family massacre twenty years earlier, Kars McIntyre, when the person believed to be responsible for the killings is released, wonders how many times she can be the girl who survived as people around her die horrible deaths
All her life, she's been the girl who survived. Orphaned at age seven after a horrific killing spree at her family's Oregon cabin, Kara McIntyre is still searching for some kind of normal. But now, twenty years later, the past has come thundering back. Her brother, Jonas, who was convicted of the murders has unexpectedly been released from prison. The press is in a frenzy again. And suddenly, Kara is receiving cryptic messages from her big sister, Marlie--who hasn't been seen or heard from since that deadly Christmas Eve when she hid little Kara in a closet with a haunting, life-saving command: Don't make a sound. As people close to her start to die horrible deaths, Kara, who is slowly and surely unraveling, believes she is the killer's ultimate target. Kara survived once. But will she survive again? How many times can she be the girl who survived?
BPL: Given in memory of Lance Shope by Brenda Shope.
Keywords: Massacre survivors -- Fiction; Murder -- Fiction; Brothers and sisters -- Fiction; Survival -- Fiction; Detective and mystery fiction; Thrillers (Fiction); Novels